THE ROLE OF PHYSICAL EDUCATION IN STRENGTHENING THE HEALTH OF STUDENTS (Neo Science Peer Reviewed Journal, 2023)
The health status of young people is the most important component of the healthy potential of the nation. Modern living conditions set us the task of forming students' conviction in the need to lead a healthy lifestyle. Moral health is determined by moral principles, which are the basis of a person's social life.